2023
DOI: 10.1088/1538-3873/acb846
|View full text |Cite
|
Sign up to set email alerts
|

In-orbit Performance of the Near-infrared Spectrograph NIRSpec on the James Webb Space Telescope

Abstract: The Near-Infrared Spectrograph (NIRSpec) is one of the four focal plane instruments on the James Webb Space Telescope. In this paper, we summarize the in-orbit performance of NIRSpec, as derived from data collected during its commissioning campaign and the first few months of nominal science operations. More specifically, we discuss the performance of some critical hardware components such as the two NIRSpec Hawaii-2RG detectors, wheel mechanisms, and the microshutter array. We also summarize the accuracy of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 91 publications
(35 citation statements)
references
References 29 publications
0
35
0
Order By: Relevance
“…The complete details of the CEERS program will be presented in Finkelstein et al (2023, in preparation), and the program data can be found at doi:10.17909/z7p0-8481 and at https:// archive.stsci.edu/hlsp/ceers. This source is one of the first to be observed and published with four JWST (Gardner et al 2023) observing modes: NIRSpec (Böker et al 2023), NIRCam (Rieke et al 2023), MIRI (Wright et al 2023), and NIRCam/ Wide-Field Slitless Spectrograph, or WFSS (Greene et al 2017). We describe these observations below and provide a summary of information about this source in Table 1.…”
Section: Datamentioning
confidence: 99%
“…The complete details of the CEERS program will be presented in Finkelstein et al (2023, in preparation), and the program data can be found at doi:10.17909/z7p0-8481 and at https:// archive.stsci.edu/hlsp/ceers. This source is one of the first to be observed and published with four JWST (Gardner et al 2023) observing modes: NIRSpec (Böker et al 2023), NIRCam (Rieke et al 2023), MIRI (Wright et al 2023), and NIRCam/ Wide-Field Slitless Spectrograph, or WFSS (Greene et al 2017). We describe these observations below and provide a summary of information about this source in Table 1.…”
Section: Datamentioning
confidence: 99%
“…For the data reduction, we began by retrieving the uncal files from the Mikulksi Archive for Space Telescopes (MAST; doi:10.17909/jzze-5611). We performed ramps-to-slopes processing on those files using the NIRSpec Instrument Pipeline Software, 11 which features a correction for "snowballs" (Böker et al 2023) and a correction for residual correlated noise in IFU data. The resulting count rate maps (rate files) were used as inputs to the JWST calwebb_spec2 pipeline with the default processing steps, including assignment of the world coordinate system, flat-fielding, and aperture correction.…”
Section: Data Reductionmentioning
confidence: 99%
“…31 We note that the GLASS-JWST program also obtained Near-Infrared Imager and Slitless Spectrograph (NIRISS; Doyon et al 2012, R. Doyon et al 2023, in preparation) spectroscopy of the cluster core covering wavelengths λ ∼ 1.1-2.2 μm. The UNCOVER program also includes spectroscopic follow-up observations with JWST's Near Infrared Spectrograph (NIRSpec; Ferruit et al 2022;Jakobsen et al 2022;Böker et al 2023), which are scheduled for 2023 July and would allow deeper spectroscopic measurements and to longer wavelengths. A2744 will also be observed with NIRCam as part of the JWST guaranteed time observation (GTO) program Prime Extragalactic Areas for Reionization and Lensing Science (PEARLS; Program ID: GTO 1176; PI: R. Windhorst;Windhorst et al 2023).…”
Section: Datamentioning
confidence: 99%